The implementation of chempuzzle in increasing students' understanding of atomic structure, elements periodic system, chemical bonding, and basic laws of chemistry concepts - Rr. Lis Permana Sari (LPPM UNY, 2009)
The aim of this study was to identify the effectiveness of Chempuzzle on increasing studentss understanding of atomic structure, elements periodic system, chemical bonding, and basic laws of chemistry concepts. This study has been done in four high school in Province DIY on 2008/2009 academic year. There are 247 students become participants of this quasi-experiment study. Instuctional methods including chempuzzle was conducted in this study came into three stage: chempuzzle introduction, chemdoku problem solving exercises, chemkuro problem solving exercises, and discussion. The data collection was devided into two steps. First, measurement of students priorknowledge and the second is measurement of students concept understanding. The result of Anacova test showed that the concept understanding of student from Gunung Kidul (Fo = 12.041; p = 0.001), Kota Yogyakarta (Fo = 6.918; p= 0.010), and Kulon Progo (Fo = 15.923; p = 0.000) were significantly different for the two groups, meanwhile those from Sleman (Fo = 1.418; p = 0.237) were not different for the two groups. This results showed that Chempuzzle is effective to be implemented on learning process of atomic structure, elements periodic system, chemical bonding, and basic laws of chemistry concepts in the three of four high school. To be an effective method on improving student concept acquisition, it need more time for preparing and introducing the game, and need teacher creativity to make the puzzle form interesting.